Presentación del Vol 4 Núm 2 (2023) - Zegarra López, Fernando Elías (2023)
Description of the content of the journal highlighting the importance of the National Defense System, its multidimensionality and the need to have qualified people in the Executive Branch, so that they can implement the National Multisectoral Security and National Defense Policy by 2030, which is not It refers neither to the Armed Forces nor to the Heads of the National Security and Defense Offices.